PELAYANAN HOME CARE : PERAWATAN LUKA TERHADAP PENERIMAAN DIRI PASIEN DIABETES MELITUS TIPE II - Dyah Restuning Prihati; Heny Prasetyorini (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2024)
Background: Home care is a health service that is carried out by professionals in the patient's residence with the aim of helping to fulfil the patient's needs in overcoming health problems. Patients with type 2 diabetes mellitus will experience changes in themselves. Each individual responds and has different perceptions of these changes. The purpose of this study was to analyse the self-acceptance of type II Diabetes Mellitus patients after being given home care services: wound care. This research method is a quasi-experimental one-group pre-post test with home care service intervention: wound care. The instrument to measure foot care behaviour used the acceptance of illness scale (AIS) questionnaire. The results showed that before being given home care services: wound care the majority experienced low self-acceptance of 19 respondents (63.3%). While after being given home care services: wound care the majority experienced moderate self-acceptance of 12 respondents (40%). Data analysis using the Wilcoxon Signed Rank Test obtained a p-value of 0.002 so that the p-value <0.05 there is a difference in foot care behaviour before and after family support-based foot care education is given to respondents. Conclusion: The results showed that there were differences in self-acceptance before and after home care services: wound care.